A prosopographic study of the New Kingdom tomb owners of Dra Abu el-Naga - Jiménez-Higueras, Ángeles, (Archaeopress Egyptology ;, 2022)
Containing the dating, kinship data and titles for each tomb owner of 54 tombs located in the southern area of the Theban cemetery of Dra Abu el-Naga during the New Kingdom, this book will prove of great assistance as a handbook or catalogue for research on New Kingdom Dra Abu el-Naga or the study of prosopography and kinship relationships.